Evropski pravni standardi manjšinskega varstva, uresničevanje in dileme razvoja - Klopčič, Vera (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2006)
EUROPEAN LEGAL STANDARDS OF MINORITY PROTECTION IMPLEMENTATION AND DEVELOPMENT DILEMMAS. In the 20th century - "the century of nations" - when great importance was ascribed to the ethnic principle and to the right of self-determination, the theory of the ethnic dimension of self-determination of nations as groups prevailed. Currently we are witnessing processes of associating and disassociating; on the one hand supranational forms of integration are gaining strength, on the other hand new states following the model of "national state" are being established, strengthening different connections at micro and local level. The author discusses the role of minorities in the future of democratic societies and within international legal regulation of human rights and minority protection. Specifically discussed is the history of the right of self-determination in the judiciary practice of the Interstate court, with special emphasis on the characteristics, important for the understanding of this right within the context of individual and collective dimensions in the field of international legal protection of human rights and minority rights.
Keywords: narodne manjšine; zaščita manjšin; pravno varstvo; pravni standardi; pravica do samoodločbe